Government Spending Multipliers in Developing Countries Evidence from Lending by Official Creditors - Kraay, Aart (The World Bank, 2012)
This paper uses a novel loan-level dataset covering lending by official creditors to developing country governments to construct an instrument for public spending that can be used to estimate government spending multipliers. Loans from official creditors (primarily multilateral development banks and bilateral aid agencies) are a major source of financing for government spending in developing countries. These loans typically finance public spending projects that take several years to implement, with multiple disbursements linked to the stages of project implementation. The long disbursement periods for these loans imply that the bulk of government spending financed by official creditors in a given year reflects loan approval decisions made in many previous years, before current-year macroeconomic shocks are known. Loan-level commitment and disbursement transactions from the World Bank's Debtor Reporting System database are used to isolate a predetermined component of government spending associated with past loan approvals. This can be used as an instrument to estimate spending multipliers for a large sample of 102 developing countries. The one-year government spending multiplier is reasonably-precisely estimated to be around 0.4, and there is some suggestive evidence that multipliers are larger in recessions, in countries less exposed to international trade, and in countries with flexible exchange rate regimes